BENTUK-BENTUK MITOS DALAM CERITA RAKYAT BANJAR THE MYTH TYPES IN BANJAR’S FOLKLORE - NFN Saefuddin (Balai Bahasa Kalimantan Barat, 2018)
The problem which is discussed in this study is how the types of myth in Banjar’s foklore are. The aim of this study is to reveal the types of myth in Banjar’s folklore. The myth in folklore is one of old literatures and is anonymous. Myth is not belong to an individual, but it is produced by a society. The dissemination was done from mouth to mouth. Generally myth has connection with story about miracle and has close relation with believing to the God and Goddess that has special relation in the society. Myth story can be seen in Banjar folklore, one of them is the story of Putri Junjung Buih that tell us about human who was born from the result of hermitage and foam. The method which is used in this study is descriptive qualitative. This method is a method to get information about narration in myth story deeply. The result gives description about type of myth in Banjar folklore, South Kalimantan.